ANATOMI DAN IDENTIFIKASI SEMBILAN BELAS JENIS KAYU DARI SULAWESI - Y I Mandang; Nenny Sumarliaai (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Gross and anatomical features of nineteen wood species from Sulawesi belonging to 15 genera and 11 family were observed, described and then compared for identification. A dichotomous key for identification were also consructed.Upright cells with pointed end were discovered in the xylary ray tissue of Koordersiodendron pinnatum Merr. This feature were never observed in any other wood species.The occurence of crystals in parenchyma of Palaquium proved not to be constant, so it should be used for identification of the genus in positive sense only.